Chronic bronchitis is associated with severe exacerbation and prolonged recovery period in Chinese patients with COPD: a multicenter cross-sectional study - Liang, Ying; Chen, Yahong; Wu, Rui; Lu, Ming; Yao, Wanzhen; Kang, Jian; Cai, Baiqiang; Zhou, Xin; Liu, Zheng; Chen, Ping; Sun, Dejun; Zheng, Jingping; et al. (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Background: Chronic bronchitis (CB) is closely associated with the frequency and severity of chronic obstructive pulmonary disease (COPD) exacerbation. However, little is known about the impact of CB on COPD exacerbations, severe and non-severe, and on recovery from an exacerbation. Methods: We conducted a nation-wide multicenter cross-sectional survey in China between September 2007 and December 2008. Eleven hospitals participated in this study. Patients’ demographic information, presence of CB, overall numbers of COPD exacerbation and severe exacerbation leading to emergency visit, hospitalization and intensive care unit (ICU) stay in the past year, recovery period following the last exacerbation, and well- or poor-recovery were recorded. Results: A total of 1,101 patients with COPD were enrolled and 890 (80.8%) had CB. Patients with CB reported more history of frequent exacerbations (≥2/patient/year) (59.6% vs. 50.7%, P=0.019) and severe exacerbation (% emergency visit ≥1: 28.0% vs. 16.6%, P=0.001; % hospitalization ≥1: 51.2% vs. 28.0%, P